Positive Impact of Physical Exercise for Managing Stereotypies in Dogs - Ostrovsky, G. (2017)
Stereotypies in dogs are repetitive behavioral patterns that occur always in the same sequence but do not play any role. This altered behavior may thus take over the animal’s life, changing its sleep patterns and eating habits. The drive to adopt the specific behavior becomes increasingly stronger, to the extent that the animal may sometimes even mutilate parts of its own body, such as the tail and limbs. The overall approach to the problem through retraining of owners, environmental modification and enrichment and proper use of psychotropics proved necessary for restoring the patients’ balance. However, it was also necessary to introduce a physical exercise routine with a canine motorized treadmill and/or daily walks. Although exercise itself may contribute to increased anxiety in the animal, the potential benefits justify considering its introduction for managing dogs with stereotypies.